Dataset: Mapping the Landscape of Cyber Law and Cyber-Harassment Research: A Comprehensive Data Analysis - Nur Riska Salsabila; Mochammad Tanzil Multazam (Proceedings of The ICECRS, 2022)
This data article presents a comprehensive analysis of cyber law and cyber-harassment-related journal articles within the field of law. The data was collected using the lens.org platform, employing keyword searches for "cyberlaw" and "cyber-harassment," and subsequently filtering the results by document type (journal articles) and subject matter (law). The final dataset comprises 143 scholarly works, which were analyzed to identify the top institutions, fields of study, authors, countries, and publishers involved in this area of research. The results reveal that Cardiff University is the most prolific institution, with psychology being the most common field of study. The United Kingdom is the most active country, and Informa UK Limited is the top publisher. This data is valuable for researchers seeking literature related to cyber law and cyber-harassment, offering insights into the prevalent themes and trends in this rapidly evolving domain. Highlights: The prevalence of psychology as the top field of study, indicating the significant impact of cyber-harassment on mental well-being. The United Kingdom's role as the most active country in publishing related research, demonstrating its commitment to addressing cyber law and harassment issues. The rapid development of cyber-harassment and its association with increased risk factors, emphasizing the need for ongoing research and preventative measures.